The relationship between childhood emotional maltreatment and disordered eating behaviors among students: Mediating role of emotion dysregulation; A cross-sectional study - Ghanei, Nasim; Pourshahriar, Hossein; Shokri, Omid (Chronic Diseases Journal, 2020)
BACKGROUND: Previous studies have shown that childhood emotional maltreatment (CEM) plays a role in development of disordered eating behaviors (DEBs). Difficulty in emotion regulation is another factor influencing disordered eating. This study was directed to examine the association between CEM and DEB among students, by considering the emotion dysregulation as a mediator. METHODS: This correlational study was conducted in form of a cross-sectional design, using structural equation modeling (SEM) to analyze the data collected from 401 non-native undergraduate students through convenience sampling method. Childhood Trauma Questionnaire (CTQ) was used to assess childhood emotional abuse and neglect. Emotion dysregulation and DEB were respectively measured using the Difficulties in Emotion Regulation Scale (DERS) and Eating Attitude Test (EAT). RESULTS: The partial mediation model of difficulties in emotion regulation in the association between CEM and DEB among male and female students had a good fit to the data. The outcomes of the gender specificity of structural relations in the model confirmed gender invariance of the structural model. All regression weights in the model were statistically significant and the CEM and emotion dysregulation variables accounted for 22%, 17%, and 35% of the variance of DEB among the entire sample, female students, and male students, respectively. CONCLUSION: The outcomes are in line with research findings suggesting a relationship between CEM and DEB and confirm the role of emotion dysregulation as a mediator. The results highlight the importance of assessment of childhood experiences in treatment of eating disorders and introduce emotion regulation as a significant target for intervention.